Diskresi Kepolisian Diluar Pengadilan dalam Rangka Penyelesaian Perkara Pencurian oleh Anak dalam Keluarga - Dody Hendra Hendra (Jurnal Suara Hukum, 2020)
Constitution of the Republic Indonesia 1945 states that Indonesia is a state of law. It is affirmed that the Republic of Indonesia is based on law (rechstaat), not for power merely (machtstaat). Children are the next generation of the nation that must be protected by their rights, so that if there is a criminal act involving children, it should not end in a prison sentence but can be settled in a certain way outside the court. Based on the consideration, the author disscuses this journal with the title "Discretion of Police outside the Court in the settlement of theft cases by children in the family". The problem of the study is about how the application and effectiveness of Police Discretion outside the Court in resolving theft cases by children in the family. In this research, the authors used legal research with an empirical juridical approach by using primary data sources obtained from interviews with National Police investigators and secondary data sources obtained by searching literature such as laws, books and legal dictionaries. The research method used isqualitative data analysis to obtain descriptive analytical data from the sources of data obtained. The conclusion is that there is no regulation which becomes the legal basis for the National Police to settle criminal cases by applying Restorative Justice approaches, especially in the crime of theft committed by child.           Keywords: Discretion, Court, Police, Theft, child